Religious differences for customers And New Products Adopation - حسوني اثير عبدالامير (Journal of Economics and Administrative Sciences, 2018)
Abstract The problem with the search at the reduction of adoption of new products, as there are three hypotheses of research have been formulated , the first one is no significant correlation between the religious and differences to customers and adopt new products, and This Study Aimed To Investigate The Relationship Between Religious differences for customers And New Products Adoption, Applied On Arab Mall Commercial Customers/ Egypt, an Analytical Model Is Developed As Guideline To Test The The Relationship Between Religious differences for customers And New Products Adoption, Aquantative Method With Deductive Approach Were Chosen In This Research . In Order To Collect Primary Data, A questionnaire Is Designed And Data Have Been Collected From Arab Mall Customers. The Spss Is Used To Process The Primary Data. Samplesize Is 600, And The Valid Questionnaire Are 521 (267 Muslim, 254 Christian) 74 % Of Sample Size. It was reached to a group of the most important conclusions That Is Religious differences for customers Positively Related To New Products Adoption . Also , It Shows That Religious differences for customers Has Appositive Effect On New Products Adoption, and we concluded the research by a set of recommendation, Need for attention to customers and defer to their suggestions and problems about the new products, which leads to the removal of obstacles faced by existing customers on the one hand, and the payment of potential customers to experience the new product and then adopted .